Recent Advances in Phalaenopsis Orchid Improvement using Omics Approaches (Plant Tissue Culture and Biotechnology, 2019)
With recent advances in high-throughput sequencing (HTS) technologies to improve plants, there is a need to release orchid specific genomic resources and platforms that are crucial for managing omics elements in systematic manner. Authors provide details about the recent developments in biotechnological techniques, genomics, transcriptomics, proteomics, metabolomics and their applications for the industrial production, propagation, conservation and manipulation of Phalaenopsis orchid.Plant Tissue Cult. & Biotech. 29(1): 133-149, 2019 (June)